2006
DOI: 10.1016/j.jacc.2005.12.066
|View full text |Cite
|
Sign up to set email alerts
|

Heart Disease Risk Determines Menopausal Age Rather Than the Reverse

Abstract: The findings support the view that heart disease risk determines age at menopause. This offers a novel explanation for the inconsistent findings on cardiovascular disease rate and its relationship to menopausal age and effects of hormone replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
3
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(124 citation statements)
references
References 46 publications
(29 reference statements)
4
110
3
3
Order By: Relevance
“…22 It has been postulated that cardiovascular risk in women was related to interactions between cardiovascular risk factors and menopause, 23 to a stronger inverse association between coronary heart disease and HDL cholesterol level in women than in men, to differences in coagulation, to differences in patterns of obesity, and to a role for hyperinsulinemia. 22,24,25 The impact of cardiovascular factors such as diabetes on risk for cardiovascular disease and for death is reported to be greater in women than in men in the GP.…”
Section: Discussionmentioning
confidence: 99%
“…22 It has been postulated that cardiovascular risk in women was related to interactions between cardiovascular risk factors and menopause, 23 to a stronger inverse association between coronary heart disease and HDL cholesterol level in women than in men, to differences in coagulation, to differences in patterns of obesity, and to a role for hyperinsulinemia. 22,24,25 The impact of cardiovascular factors such as diabetes on risk for cardiovascular disease and for death is reported to be greater in women than in men in the GP.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies support the hypothesis that the reduction of estrogen would be the main factor for the increase of this incidence, directly associated with aging and biological aging, which itself already contributes to the increase of health problems. However, Kok et al (2006) [30] conducted a study with Framingham's data to investigate whether cardiovascular risk profile could accelerate menopause. The results showed that the risk of heart disease determines the age of menopause.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, POI is potentially associated with both more severe and different health risks than natural menopause. Women entering menopause early seem to be at increased risk of cardiovascular disease (6). In addition, impaired endothelial dysfunction, an early stage of atherosclerosis, has been described in young women with POI (7).…”
mentioning
confidence: 99%